Maintenance of mouse trophoblast stem cells in KSR-based medium allows conventional 3D culture - Shuai SUN; Shota YANO; Momo O NAKANISHI; Michiko HIROSE; Kazuhiko NAKABAYASHI; Kenichiro HATA; Atsuo OGURA; Satoshi TANAKA (The Journal of Reproduction and Development, 2021)
Mouse trophoblast stem cells (TSCs) can differentiate into trophoblast cells, which constitute the placenta. Under conventional culture conditions, in a medium supplemented with 20% fetal bovine serum (FBS), fibroblast growth factor 4 (FGF4), and heparin and in the presence of mouse embryonic fibroblast cells (MEFs) as feeder cells, TSCs maintain their undifferentiated, proliferative status. MEFs can be replaced by a 70% MEF-conditioned medium (MEF-CM) or by TGF-ß/activin A. To find out if KnockOutTM Serum Replacement (KSR) can replace FBS for TSC maintenance, we cultured mouse TSCs in KSR-based, FBS-free medium and investigated their proliferation capacity, stemness, and differentiation potential. The results indicated that fibronectin, vitronectin, or laminin coating was necessary for adhesion of TSCs under KSR-based conditions but not for their survival or proliferation. While the presence of FGF4, heparin, and activin A was not sufficient to support the proliferation of TSCs, the addition of a pan-retinoic acid receptor inverse agonist and a ROCK-inhibitor yielded a proliferation rate comparable to that obtained under the conventional FBS-based conditions. TSCs cultured under the KSR-based conditions had a gene expression and DNA methylation profile characteristic of TSCs and exhibited a differentiation potential. Moreover, under KSR-based conditions, we could obtain a suspension culture of TSCs using extracellular matrix (ECM) coating-free dishes. Thus, we have established here, KSR-based culture conditions for the maintenance of TSCs, which should be useful for future studies.